Adubação fosfatada associada a microrganismos solubilizadores de fósforo aplicados à cultura da soja - MATEUS HENRIQUE BARBOSA MORATA (2024)
The soybean cultivation system is complex and demands a set of practices aimed at minimizing and mitigating adverse effects, such as pests, diseases and climate. Among the inputs used, products based on microorganisms stand out, especially phosphorus solubilizers. The objective of this work was to verify the influence of the use of phosphorus-solubilizing bacteria on agronomic characteristics and productivity in soybean cultivation at different doses of phosphorus in the Northeast region of Mato Grosso do Sul. The design used was that of randomized blocks in subdivided plots, with four inoculations of solubilizers; T1 - Control (mineral fertilizer), T2 - Bacillus. licheniformis (200 mL ha-1), T3 - Pseudomonas + Azo (300 mL ha-1) and T4 - B. megaterium + B. subtilis 200 mL ha-1, with four replications. In addition to four doses of mineral fertilizer (0, 50, 75 and 100%) that were applied pre-planting. Plant height and first pod insertion height, internode length, number of pods per plant, number of grains per plant, weight of one hundred grains, and grain productivity were evaluated. The use of phosphorus-solubilizing bacteria provides greater plant height, number of pods per plant and weight of one hundred grains, which are agronomic characteristics indirectly related to crop productivity. Phosphorus doses used in isolation influence the number and length of internodes and productivity when using a 50% dose.